An Analysis on The Belief of Sembalun People Towards Ngayu-Ayu Ceremony: Analisis Kepercayaan Masyarakat Sembalun Terhadap Upacara Ngayu-Ayu - Kurniawan, Taufiq; Siti Danti; Lala Nining Indrawati (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2023)
Culture is a guideline relationship between people or groups that function as a forum for sharing feelings and other lives. It is also used as a life guide and differentiator between humans and animals. For this reason, each region has differences and uniqueness that are highlighted depending on their respective regions according to the needs of the community. This study aims to analyze the goals of the Sembalun people when carrying out the Ngayu-ayu traditional activities. The design used in this research was qualitative descriptive. The data were obtained by using interviews and documentation techniques. The researcher used open interview. It was conducted to get information from the respondents based on the problem and object being interviewed. Documentation is used to obtain the data by collecting all kinds of legal documents such as notes, reports and photography. The results and discussions will be discussed further.